USAGE OF INTELLECTUAL TECHNOLOGY FOR AUTOMATIZATION OF TEACHING CONTROL - Mazurok Т.Л. (Journal of Information Technologies in Education (ITE), 2013)
The results of the research to identify the features usage of intellectual technologies for to realize of a synergetic model of automatization individual teaching control.